“It doesn’t require blood!”: Perceptions around non-invasive malaria testing tools in Indonesia, Peru, and Rwanda - Vanessa Fargnoli; Serafina Calarco; Catherine Thomas; Caroline Thomas; Claudius Novchovick Mone Iye; Valerie A. Paz Soldan; Amy Celeste Morrison; Janvier Serumondo; Ladislas Nshimiyimana; Yvonne Delphine Nsaba Uwera; Elena Marbán-Castro; Sonjelle Shilton; et al. (PLoS ONE, 2026)
Malaria remains a major global health challenge. Prompt, accurate diagnosis is crucial for effective case management. Current diagnostic approaches rely on invasive or minimally invasive sampling via venous or fingerpick blood draw, posing a risk to healthcare workers via the handling of potentially infectious body fluids. They may also be a barrier to recipients, particularly in malaria-endemic areas where there is routine testing of non-symptomatic individuals. Non-invasive tests based on saliva, exhaled volatile organic compounds (VOCs), and transdermal detection have the potential to increase case detection and linkage to care while reducing biosafety risks. Knowledge gaps exist regarding the feasibility and acceptability of these tools. This qualitative study, conducted in Indonesia, Peru, and Rwanda, aimed to generate evidence from end-users around the potential adoption of non-invasive diagnostic technologies, to determine whether these technologies are fit for purpose. Between October and November 2023, 24 semi-structured interviews were conducted with stakeholders and professionals working at borders, and 16 focus group discussions were conducted with caregivers of children under 5 years, pregnant women, healthcare workers, teachers and other community members (139 participants in total). The comfort non-invasive approaches offer to recipients of care was widely noted, especially compared with blood draw, which is considered painful for children. Ease of use and rapid diagnostic capabilities enabling real-time disease diagnosis were perceived as particularly beneficial in remote areas with limited healthcare infrastructure. Device portability was seen as a game-changer. Major concerns were the lack of information regarding the accuracy of non-invasive tools compared with established methods, the lack of trust in tests targeting specimens other than blood products, and their inability to differentiate between malaria species. Early engagement with stakeholders in the development of novel interventions is essential to ensure that end products meet the needs of communities.